The Effect of Income on Religiousness - Thomas Buser (Center for Economic Studies and ifo Institute (CESifo), 2014)
How does income affect religiousness? Using self-collected survey data, we estimate the effects of income on religious behaviour. As a source of exogenous income variation we use a change in the eligibility criteria for a government cash transfer in Ecuador and apply a regression discontinuity strategy to estimate causal effects. We find significant effects of income on religiousness. Households that earn more go to church more often. Households that earn more are also more likely to be members of an evangelical community rather than of the mainstream catholic church.
Keywords: Z12; 330; religion; income effects; regression discontinuity